Les dialectismes dans Balerina, Balerina de Marko Sosič et leur traduction française - Vaupot, Sonia (Ars et humanitas, 2023)
he novel Balerina Balerina by Marko Sosič, published in 1997, has won several li-terary prizes. However, this Slovenian work resists translation because of the author’s personal writing, but also because of the literary value of the Slovenian and Italian coastal dialect, which the author mixed with standard Slovenian, creating a special poetic prose. In this article we discuss the difficulties of translating or adapting this dialect into French, and then we analyse the translator’s choices and the procedures used to solve the difficulties arising from the presence of dialect elements in the novel.
Keywords: Italija; literarno prevajanje; narečje; narečna slovenščina; prevajanje v francoščino; Slovenija; Sosič, Marko